Pengaruh Kecerdasan Emosional, Motivasi dan Disiplin Kerja Terhadap Kinerja Pegawai KPU Kota Probolinggo - Alex Salamullah; Mohammad Iskak Elly; Junaidi Junaidi (Universitas Panca Marga, 2023)
The performance of KPU Probolinggo City employees can be maximized if conditions are met properly. One of the factors increasing performance is managing emotional intelligence, maintaining motivation and increasing work discipline. This study aims to determine the effect of emotional intelligence, motivation and work discipline on employee performance partially on the performance of KPU Probolinggo City employees. This research method is quantitative with a causal associative approach. The population of this research is all employees, totaling 32 employees. The sampling technique uses non-probability sampling, namely saturated sampling. The sample in this study were 32 respondents. Source of data used in this research comes from primary data and secondary data. Data were collected through questionnaires and completed through data analysis methods in the form of validity tests, reliability tests, classical assumption tests, multiple regression analysis, coefficient of determination (R-Square) and hypothesis testing. The results of the study show that emotional intelligence has a positive and significant effect on employee performance. And motivation has a positive and significant effect on employee performance and work discipline has a positive and significant effect on employee performance.